The Pulmonary Artery Pulsatility Index Provides No Additional Prognostic Information in Pediatric Pulmonary Arterial Hypertension - Faye E. Smits; Chantal Lokhorst; Marlies G. Haarman; Mark-Jan Ploegstra; Rolf M. F. Berger; Johannes M. Douwes (MDPI AG, 2024)
Background/Objectives: The pulmonary artery pulsatility index (PAPi, calculated as (SPAP − DPAP)/mRAP) has been suggested as a measure of right ventricular-vascular coupling (RVVC) and as a prognostic parameter in cardiovascular conditions, particularly right ventricular failure. This retrospective study investigated the relationship between the PAPi and its components with disease severity parameters, the RVVC, and clinical outcomes in children with pulmonary arterial hypertension (PAH). Methods: We analyzed data from 111 children from the Dutch National Registry with PAH. The PAPi (median 6.0 [3.9-8.3]) was calculated from heart catheterization data and the RVVC was determined as the TAPSE/sPAP ratio via echocardiography (0.25 ± 0.12 mm/mmHg). Disease severity was characterized by clinical, hemodynamic, and laboratory data. Cox proportional hazard modeling assessed the PAPi's predictive value for transplant-free survival. Results: There was no correlation between the RVVC and PAPi (R = −0.208, p = 0.111, n = 60). The PAPi correlated negatively with uric acid (R = −0.387, p < 0.001) but not with other disease severity parameters. Mean right atrial pressure correlated with multiple disease severity indicators. Transplant-free survival rates at 1, 3, and 5 years were 87%, 79%, and 73%, respectively. Neither the PAPi nor its components correlated with transplant-free survival. Conclusions: In conclusion, the PAPi does not correlate with the RVVC and this study could not demonstrate any prognostic value of the PAPi regarding disease severity or outcomes in children with PAH, challenging its utility in this population.